An efficient blockchain‐based approach for cooperative decision making in swarm robotics. Issue 1 (19th December 2019) - Singh, Pranav K.; Singh, Roshan; Nandi, Sunit K.; Ghafoor, Kayhan Z.; Rawat, Danda B.; Nandi, Sukumar
Abstract : Swarm robotics is an emerging robotic domain that aims to accomplish complex tasks with the cooperative effort of a group of simple robots. These robots communicate and share information to coordinate their actions for achieving a common goal. However, existing mechanisms of control and communications are not very secure, efficient, and also rely on centralized controlling authority. It is not flexible, and also has low transparency and tracking capabilities. Blockchain, a decentralized technology based on peer to peer communication along with smart contracts, can be a potential contender for addressing these challenges. However, blockchains are resource‐intensive and not found suitable for resource‐constrained devices. We propose a blockchain‐based framework, which is based on Proof‐of‐Authority (PoA) consensus mechanism to ensure efficiency. We experiment with test‐bed implementation using RaspberryPi. The results obtained demonstrate that the PoA mechanism is not a resource‐hungry one (unlike other state‐of‐the‐art consensus mechanisms). The blockchain with PoA in swarm robotics can provide the necessary security, transparency, decentralization, reliability, autonomy, etc.